Prenatal diagnosis of congenital megalourethra: a rare anomaly - Singh, Neha; Bansal, Vandana; Damania, Kaizad R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Congenital megalourethra is a rare urogenital malformation characterised by pathological elongation and dilatation of penile urethra. It is a form of functional obstructive uropathy which is associated with significant urological and sexual dysfunction secondary to hypoplasia or absence of corpora cavernosa and spongiosa. We report a case of megalourethra in one of the dichorionic diamniotic twin diagnosed prenatally in a young primigravida. Initial ultrasound report suggested two different diagnoses i.e. omphalocoele and gastroschisis. Later, diagnosis of congenital megalourethra was made on detailed ultrasound examination by our fetal medicine consultant. Postnatal gross and ultrasonographic examination confirmed the prenatal diagnosis. In the present case report, we have emphasized proper perineal anatomical ultrasound examination which revealed a megalourethra. Although this anomaly is not lethal in isolation, but it has worse prognosis in presence of other associated structural anomalies. This anomaly also raises the controversy regarding disclosure of sex of foetus in countries like India where sex disclosure is prohibited by law. As this condition typically affects male foetuses and significantly affects sexual function, it may be necessary to reveal fetal sex for appropriate counselling and prognostication to prospective parents. Ethical dilemma arises for practising clinicians while dealing with isolated forms of megalourethra whether to offer termination of pregnancy on the grounds of having significant impact on sexual life due to erectile dysfunction. Anorectal malformation is often associated with megalourethra, although suspected in the present case, can be difficult to identify antenatally prior to 20 weeks (the time limit up to which legal termination can be performed in India). These issues have been highlighted in the present report.